Adobe Creative Cloud all-in-one for dummies - Smith, Jennifer; Smith, Christopher (Wiley, 2017)
Adobe Creative Cloud is the most popular suite of tools among creative professionals, and a valuable resource you can use to fulfill all of your design goals. Ready to get started? This text, written by designers for designers, will provide you with expert instruction that spans seven mini-books, with helpful information that can grant insight regardless of your current level of knowledge.
Previous edition: published as Adobe Creative Cloud design tools all-in-one for dummies by Jennifer Smith, Christopher Smith, Jen DeHaan, and Fred Garantabee. 2013. - Includes index. - Title detail screen (OverDrive, viewed December 21, 2017)
Keywords: Computer graphics -- Computer programs; Cloud computing; Infographie; Logiciels; Infonuagique; Computer graphics; Computer programs